2011
DOI: 10.1007/s10147-011-0254-y
|View full text |Cite
|
Sign up to set email alerts
|

Clinical practice and outcome of radiotherapy for esophageal cancer between 1999 and 2003: the Japanese Radiation Oncology Study Group (JROSG) Survey

Abstract: Although the overall survival rates for stage I esophageal cancer were excellent, a significant disparity in survival rates was noted among the institutions for stage II-IVA tumors treated by CRT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
1
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 28 publications
(53 reference statements)
0
15
1
1
Order By: Relevance
“…In the present study, 28 patients who did not undergo additional OP showed only 3.5% of local relapse without any death caused by post-ESD complications. This result was better than the rates of previous reports (6,7) (Table 7). Moreover, the rate was better than the rate of the Kobe University Hospital study of CRT treatment for clinical stage I esophageal SQC (local relapse rate: 14%, n=21).…”
Section: Discussioncontrasting
confidence: 78%
See 2 more Smart Citations
“…In the present study, 28 patients who did not undergo additional OP showed only 3.5% of local relapse without any death caused by post-ESD complications. This result was better than the rates of previous reports (6,7) (Table 7). Moreover, the rate was better than the rate of the Kobe University Hospital study of CRT treatment for clinical stage I esophageal SQC (local relapse rate: 14%, n=21).…”
Section: Discussioncontrasting
confidence: 78%
“…Acute and late cardiopulmonary toxicity due to CRT is a critical issue (34)(35)(36) and is observed in 2-10% of the patients according to previous reports (6,7,(8)(9)(10)(11). To prevent it, not only the improvement of radiation techniques, but also a reduction of the radiation dose to the esophagus, heart and lung are important.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In prospective studies of definitive CRT for unresectable esophageal cancer, the complete response (CR) rate of T4 tumors ranged from 15-32 %, and 3-year overall survival rates of approximately 20 % have been reported [3][4][5]. A retrospective survey of 9 major Japanese institutions revealed median 3-and 5-year overall survival rates of 21 % (range 10-36 %) and 19 % (range 0-31 %), respectively, for unresectable stage III-IVA tumors by definitive CRT [6].…”
Section: Introductionmentioning
confidence: 97%
“…[15][16][17] No tratamento do cancro do esófago, a radioterapia aplicada isoladamente, ou após quimio-sensibilização, como tem sido a nossa preferência, tem demonstrado resultados interessantes, apesar de não ser desprovida de complicações graves e poder necessitar de salvage surgery num número significativo de casos. [18][19][20][21][22][23] A intenção deste trabalho foi apresentar os resultados da estratégia multimodal de tratamento do cancro do esó-fago, tendo sido geralmente decidida a opção da componente operatória do processo com base na localização do tumor.…”
Section: Introductionunclassified